2011
DOI: 10.5539/ibr.v4n4p286
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of The Interest Rate Volatility on Turkish Money Demand

Abstract: This study aims to examine, especially the effects of interest rate (time deposit and treasury bills) volatilities on the demand for money in case of Turkey for 1987Turkey for : 1-2007: 3 period. Quarterly data of all variables are used as the research data and Pesaran, Shin and Smith (2001) 's bound test is used as the research method. In computing interest rate volatilities, moving-sample standart deviation method which is proposed by Kenen and Rodrik (1986) and Koray and Lastrapes (1989) is used. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Economic theory indicates that interest rate volatility also increases the demand for money. Any factor that positively affects the demand for money can adversely affect the economy through its negative effect on nominal income (Celikoz & Arslan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic theory indicates that interest rate volatility also increases the demand for money. Any factor that positively affects the demand for money can adversely affect the economy through its negative effect on nominal income (Celikoz & Arslan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature exists concerning examining the effect of the interest rate volatility or the exchange rate volatility on money demand. Celikoz and Arslan (2011) studied the relationship between the interest rate volatility and the demand for money for Turkey. Their study showed that the interest rate volatility was not statistically significant and had a positive relationship with the demand for money.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the association between monetary policy and the exchange rates is considered an important issue for the literature. Studies in the literature that have examined monetary policy variables and the domestic currency have varied both theoretically and empirically (Akar and Icek, 2015;Saraç and Karagöz;2011, Çeliköz, 2011Shastriet et al, 2013;Sensoy and Sobaci, 2014;Andria et al, 2017). However, few studies have examined the impact of economic crises on the relationship between monetary policy and exchange rates in emerging economies like Turkey, which is considered to be one of the countries that suffered from this crisis (Yuksel, 2016).…”
Section: Introductionmentioning
confidence: 99%